Sociologia da deficiência : vozes por significados e práticas (mais) inclusivas - Harlos, Franco Ezequiel (Universidade Federal de São Carlos, 2012)
In this research aim systematize stories and theories associated with the Sociology of Disability, and identify, voices to rethink the meaning of disability and practices of Special Education aimed at people in situation disabilities. For this, we developed theoretical research, based on bibliographical research and documentary developed based on 48 publications (articles, books and documents) compiled primarily from the journal Disability and Society, of Association Spanish of Sociology of Disability and the database of the Centre of Disability Studies, University Leeds. The works were compiled analyzed by reading, annotated elements, dismemberment of these annotated elements in parts (passages, phrases, quotes) categorization, meeting these parts separate units with common characteristics and the naming of these units under a name that characterizes. The first of the units identified in the main focuses interpretations adopted by the Health Sciences (Medical Paradigm) to think about disability; the second, in stories associated with the formation of the Sociology of Disability; and the third in the multiple faces of theoretical Sociology of Disability. The process of systematization of units allowed us to unveil a sociological paradigm of interpretation of disability, and this paradigm provides voices for more inclusive practices.
Keywords: Educação especial; Sociologia; Deficiência; Sociologia da Deficiência; Estudos da Deficiência; Sociology of Disability; Special Education; People in situation from disability; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL